3D Printing based on Photopolymerization and Photocatalysts: Review and Prospect. Issue 8 (14th April 2022) - Li, Jia; Boyer, Cyrille; Zhang, Xuewen
Abstract: 3D printing is a fabrication method that has attracted worldwide attention in recent years, providing a convenient and economical method for the fabrication of 3D structures. With the development of this technology and the reduction of operating costs, the application of 3D printing is greatly expanded. This paper focuses on the application progress of 3D printing in the preparation of photocatalysts. Considering the advantage that photopolymerization‐based 3D printing technology can better control the structure and active component distribution of photocatalytic products, the realization possibility of one‐step digital light processing (DLP) printing photocatalyst products is particularly prospected. In addition, the latest research progress of photocatalytic materials and 3D printing technology is also summarized, and the problems that need to be broken through in the future development of DLP‐3D printing technology are discussed. Abstract : This paper reviews the related research on the preparation of products with photocatalytic activity using 3D printing technology. Based on the related research results of digital light processing (DLP) printing and photocatalysts, one‐step DLP printing photocatalytic products are prospected.